Using GIS as an interactive marine mineral resources model for assessing economic viability : Algoa Bay as a case study - Sinclair, David Alexander (Stellenbosch : Stellenbosch University, 2012)
Research report (M. Sc.) -- University of Stellenbosch, 1998.